2013
DOI: 10.1002/jor.22500
|View full text |Cite
|
Sign up to set email alerts
|

A novel mouse model of trauma induced heterotopic ossification

Abstract: Severe soft tissue trauma is associated with heterotopic ossification (HO), the abnormal deposition of bone at extraskeletal sites. The pathophysiology of the development of trauma-induced HO remains largely unknown due in part to the lack of appropriate animal models. In this study, we sought to develop a new trauma-induced HO mouse model using muscle impact injury combined with low dose BMP-2. BMP-2 at doses ranging from 0 to 2 mg was injected into quadriceps muscles of adult male C57/BL6 mice. Animals then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 29 publications
3
35
0
Order By: Relevance
“…On the other hand, bone injury (osteotomy) alone or in combination with muscle injury increased the proportion of muscle-derived MSCs in the total population of M-MSCs and the osteogenic potential of M-MSCs. This is consistent with a recently published study, in which muscle injury alone failed to induce HO [35] . But muscle injury and the application of a low dose of BMP-2 (bone morphogenetic protein-2), which could not induce ossification alone, induced robust HO.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, bone injury (osteotomy) alone or in combination with muscle injury increased the proportion of muscle-derived MSCs in the total population of M-MSCs and the osteogenic potential of M-MSCs. This is consistent with a recently published study, in which muscle injury alone failed to induce HO [35] . But muscle injury and the application of a low dose of BMP-2 (bone morphogenetic protein-2), which could not induce ossification alone, induced robust HO.…”
Section: Discussionsupporting
confidence: 93%
“…Third, we only evaluated HO BV at a single time point-2 wk after BMP-2 injection in this study. This time point was chosen based on the time course of BMP-2-induced HO we tested in C57/BL6 mice previously [16], in which we found that HO develops no later than 2 wk after BMP-2 injection. However, the mice we used for the previous time course study did not receive surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that bone morphogenetic proteins (BMPs) can sufficiently induce HO in mice [15]. Based on this finding, we have recently developed a mouse model of trauma-induced HO by combining intramuscular injection of a small dose of BMP-2 with focal muscle injury [16]. However, this model does not include an SCI component.…”
Section: Introductionmentioning
confidence: 99%
“…There are also several modalities to recreate pathological ossifications in animal models, including the overexpression or inhibition of mole cular osteoinductive factors, trauma induction, and heterotopic implantation. [16][17][18] However, some of these models are not fully representative of the pathological states, requiring the use of a large number of animals; or are too complex to allow the isolation of individual contributing factors in early phase bone formation, which makes it objectively difficult to answer some essential questions on biological ossification. [16] Developing novel ways to produce ossified tissue is essential for several scientific reasons.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] However, some of these models are not fully representative of the pathological states, requiring the use of a large number of animals; or are too complex to allow the isolation of individual contributing factors in early phase bone formation, which makes it objectively difficult to answer some essential questions on biological ossification. [16] Developing novel ways to produce ossified tissue is essential for several scientific reasons. From a biological perspective, new models will help to develop a deeper understanding of the fundamental processes underlying both early bone development and the pathological ossification events following trauma or injury.…”
Section: Introductionmentioning
confidence: 99%